Conditional potency is a hallmark of viral protein-derived toxic peptides. (March 2017) - Tang, Man; Li, Xiaoxia; Li, Qizhang; Zhou, Yanchao; Pan, Wen; Gao, Jiayang; Ye, Zi-wei; Weng, Shaoping; Liu, Qiuyun; He, Jianguo; He, Zhumei
Abstract: Viral infections are major ongoing challenges to mankind. The theory of cytokine storm cannot fully account for the virulence of some highly infectious viruses with high mortality rates. Although numerous viruses are capable of lysing animal and human cells in vivo, viral protein-derived peptides are mostly mild in standard culture conditions in in vitro assays. A hypothesis is postulated that conditional potency of viral protein-derived toxic peptides could at least in part explain cell senescence upon viral infections. The hypothesis can be tested with full length viral proteins against microbial and mammalian cells in various media. Viral protein injections to live animals may reveal that they are critical factors underlying cell destructions when protein degradation pathways and cytokine levels are controlled. Stimulation of autophagy could enhance current viral therapies by recycling toxic viral proteins.